2020
DOI: 10.1021/acsami.9b19638
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Microenvironment for Endogenous Neural Regeneration after Spinal Cord Injury by Reassembling Extracellular Matrix

Abstract: The formation of a fluid-filled cystic cavity after spinal cord injury (SCI) is a major obstacle for neural regeneration. In this study, the post-SCI cavity was bridged by a functional self-assembling peptide (F-SAP) nanofiber hydrogel coupled with growth factor “cocktail”. A sustained release of growth factors was achieved by carefully tailoring the physical hindrances and charge-induced interactions between the growth factors and the peptide nanofibers. Such an engineering microenvironment elicited axon rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 36 publications
3
56
0
Order By: Relevance
“…In recent years, it has reported that ES can enhance the expression of brain-derived neurotrophic factor (BDNF) by activating the Ca 2+ and Erk signaling pathways (Wenjin et al, 2011). Specifically, levels of specific nerve growth factors or neurotrophic factors are downregulated in animal models of sciatic nerve injury, and the application of exogenous nerve growth factors or neurotrophic factors have a positive effect on the repair of nerve defects (Tajdaran et al, 2018;Liu et al, 2020). It is a common method to directly introduce exogenous neurotrophic factors into tissue engineered-nerve guide conduits (Labroo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has reported that ES can enhance the expression of brain-derived neurotrophic factor (BDNF) by activating the Ca 2+ and Erk signaling pathways (Wenjin et al, 2011). Specifically, levels of specific nerve growth factors or neurotrophic factors are downregulated in animal models of sciatic nerve injury, and the application of exogenous nerve growth factors or neurotrophic factors have a positive effect on the repair of nerve defects (Tajdaran et al, 2018;Liu et al, 2020). It is a common method to directly introduce exogenous neurotrophic factors into tissue engineered-nerve guide conduits (Labroo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is a polypeptide secreted by neurons, glial cells, and their innervating tissues (Xiao et al, 2009). BDNF maintains and promotes the development, differentiation, growth, and regeneration of various neurons (Lopes et al, 2017;Liu et al, 2020). It has been reported that the BDNF is synthesized in neurons and released from the surface of axon, the polarity of Schwann cells can be initiated by p75NTR which activated by BDNF, eventually led to the formation of myelin sheath by Schwann cells surrounding axon (Jonah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, single neurotrophic factor is often not very effective ( Li et al, 2006 ; Cangellaris and Gillette, 2018 ). Various endogenous neurotrophic factors for nerve regeneration were reported ( Tajdaran et al, 2018 ; Liu et al, 2020 ). Among them, BDNF can promote the myelinization of neogenesis nerve ( Lopes et al, 2017 ), GDNF can protect motor neurons from injury caused by nerve transection, and improve the re-innervation function of nerves ( Eggers et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using patient-derived cells reduces immune responses of the body to the hydrogel implant. Furthermore, endogenous stem cells inside the injured tissue may be stimulated by the implanted modified hydrogel to proliferate and differentiate into the required cell types (Liu et al, 2020). On the other hand, the patient-derived cells may be burdened by the same neuropathological deficits that cause the neurodegenerative disease.…”
Section: Hydrogels As Matrices For Cell Cultivationmentioning
confidence: 99%